Ultrastructural Studies of H-1 Parvovirus Replication VI. Simultaneous Autoradiographic and Immunochemical Intranuclear Localization of Viral DNA Synthesis and Protein Accumulation - Singer, Irwin I. (1978)
The localization of H-1 viral replicative-form double-stranded DNA and progeny single-stranded DNA replication in parasynchronously infected, simian virus 40-transformed newborn human kidney cells was studied with high-resolution electron microscope autoradiography (80-nm silver grains). We analyzed wild-type H-1 and ts1 H-1 (a conditional mutant defective in progeny single-stranded DNA synthesis). The proportion of the total DNA synthesis that was viral was estimated to be >90% by comparing the amount of [(3)H]thymidine uptake in cultures infected with wild-type H-1 versus ts14 (an H-1 mutant defective in DNA replication). Simultaneous staining with cytochrome c-conjugated anti-H-1 immunoglobulin G was performed to ensure that cells incorporating [(3)H]thymidine (2- to 60-min pulses) were H-1 infected. The sites of H-1 replicative-form (in ts1-infected cells) and progeny (in wild-type-infected cells) DNA synthesis were identical. Immunospecifically labeled nuclei at the earliest stages of infection exhibited dense clusters of silver grains over material extruded from nucleolar fibrillar centers. These foci became larger with increasing cellular damage, forming a limited number of H-1 DNA synthetic centers in the euchromatin. Each island-like focus was surrounded by tufts of heterochromatin containing high concentrations of unassembled H-1 capsid proteins. In late phases of infection, the heterochromatin became completely marginated, and the nucleoplasm contained only euchromatin that exhibited randomly distributed sites of H-1 DNA replication. This indicates that H-1 DNA synthesis begins at localized euchromatic or nucleolar sites and then spreads outward. Immunostained heterochromatin and nucleolar chromatin never incorporated [(3)H]thymidine. Our results suggest that H-1 proteins and cellular cofactors associated with the fibrillar component of the nucleolus and the euchromatin may play a role in the regulation of H-1 DNA synthesis.